Gratitude and work engagement: The mediating role of employee resilience - Endro Puspo Wiroko; Dwi Sugiharti (INSPIRA: Indonesian Journal of Psychological Research, 2022)
This study explores the relationship between perceived gratitude and work engagement in Indonesia and examines whether employee resilience mediates the relationship between perceived gratitude and work engagement. This study utilizes an online self-administered questionnaire that includes established measures associated with perceived gratitude, employee resilience, and work engagement–in addition to various demographic questions. The study sample consists of 205 respondents working as merchandisers in Fast Moving Consumer Goods (FMCG) field under outsourcing companies. This study applies a mediation model in Hayes Process to examine the data. The findings suggest that perceived gratitude is positively related to employee resilience, while employee resilience is positively associated with work engagement. In addition, employee resilience mediates the relationship between perceived gratitude and work engagement. Based on the findings, outsourcing companies are encouraged to deliver workplace-perceived gratitude training to make their employees psychologically resilient, leading to more engagement at work. The present study’s findings contribute to the literature on work engagement by explaining how perceived gratitude as a bottom-up strategy can help employees be more engaged in their work.